تأثير مواعيد الزراعة في نمو وإنتاج الملفوف الأحمر Brassica oleracea var. capitata, form rubra - سمرة, بديع; علي, ثراء (Latakia University Journal -Biological Sciences Series, 2018)
نفذ البحث في قرية حبيت التابعة لمنطقة الحفة (محافظة اللاذقية). ترتفع القرية 300م عن سطح البحر. أجريت الدراسة على هجين الملفوف الأحمر Ruby King F1 خلال الموسم الزراعي 2016-2017 بهدف تحديد أثر موعد الزراعة في نمو وإنتاج الملفوف الأحمر. شملت الدراسة 5 معاملات عبارة عن 5 مواعيد زراعية مختلفة في أواسط كل من أشهر أيار، حزيران، تموز، آب، وأيلول. صممت التجربة وفق تصميم القطاعات العشوائية الكاملة بأربعة مكررات وبمعدل 20 نبات في المكرر الواحد. شملت قراءات التجربة : شكل الرأس، حجمه، وزنه وصلابته، طول الساق الداخلية، إنتاجية وحدة المساحة، نسبة الإنتاج التسويقي من الإنتاج الكلي، كمية فيتامينC أظهرت النتائج تفوق الزراعة في شهري آب و أيلول على باقي المعاملات وبفروق معنوية من حيث مؤشرات النمو الخضرية والإنتاجية (مساحة المسطح التمثيلي، حجم الرأس، وزنه وصلابته، إنتاجية وحدة المساحة، نسبة الإنتاج التسويقي) حيث بلغت الإنتاجية (آب، أيلول) على التوالي(3654 , 3394.8) كغ/دونم. في حين تفوقت مواعيد الزراعة الأخرى (أيار، حزيران، تموز) وبفروق معنوية في كمية فيتامين C التي بلغت على التوالي (99.58 ، 98.68، 97.82) ملغ/100غ مادة طازجة. The research was conducted in village Habbet in Hafa (Lattakia region) 300 meters above sea level during the period of 2016-2017 the plant material of the research is red cabbage Ruby King F1 hybrid in order to study the effect of planting date on growth and productivity of red cabbage. The study consisted of five different planting dates during the med of May, June, July, August and ,September months The completely randomized block design was used with four replications and twenty plants in replication . The study contains indicators) :leaf surface area, shape, volume, solidity and weight of cabbage heads, inner stem length, total and marketable yield, percentage of marketable yield and content of vitamin C) The results showed that planting treatment during August and September gave the superior results with significant difference in vegetative and productive indicators: leaf surface area, solidity and weight of cabbage heads, total yield (3654 ,3394.8) kg/d respectively, marketable yield and percentage of marketable yield. While The planting during May, June, July was superior on content of vitamin C which was respectively (99.58, 98.68, 97.82 ( ml/100g with significant difference.